2020
DOI: 10.1093/cercor/bhaa231
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Interlaminar Astrocytes Are Generated Prenatally, Mature Postnatally, and Express Unique Markers in Human and Nonhuman Primates

Abstract: Interlaminar astrocytes (ILAs) are a subset of cortical astrocytes that reside in layer I, express GFAP, have a soma contacting the pia, and contain long interlaminar processes that extend through several cortical layers. We studied the prenatal and postnatal development of ILAs in three species of primates (rhesus macaque, chimpanzee, and human). We found that ILAs are generated prenatally likely from radial glial (RG) cells, that ILAs proliferate locally during gestation, and that ILAs extend interlaminar pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 45 publications
(60 reference statements)
4
40
0
2
Order By: Relevance
“…Golgi staining reveals the entire coarse morphology of astrocytes, but stains at random, and so cannot reveal astrocyte densities in the human brain. Golgi studies identified interlaminar astrocytes, a cortical astrocyte subtype with a unique morphology and molecular profile in the human and non‐human primate cortex (Colombo & Reisin, 2004; Falcone et al, 2020). Golgi studies also led to the hypothesis that human astrocyte morphology has physiological relevance, as astrocyte volume was found—much like the conductive properties of neuronal axons—to adhere to a length constant, that may maintain their potassium buffering and metabolic capacity with respect to cell size (Reichenbach, Siegel, Senitz, & Smith, 1992; Siegel et al, 1991).…”
Section: Methods For Visualizing Human Astrocytesmentioning
confidence: 99%
“…Golgi staining reveals the entire coarse morphology of astrocytes, but stains at random, and so cannot reveal astrocyte densities in the human brain. Golgi studies identified interlaminar astrocytes, a cortical astrocyte subtype with a unique morphology and molecular profile in the human and non‐human primate cortex (Colombo & Reisin, 2004; Falcone et al, 2020). Golgi studies also led to the hypothesis that human astrocyte morphology has physiological relevance, as astrocyte volume was found—much like the conductive properties of neuronal axons—to adhere to a length constant, that may maintain their potassium buffering and metabolic capacity with respect to cell size (Reichenbach, Siegel, Senitz, & Smith, 1992; Siegel et al, 1991).…”
Section: Methods For Visualizing Human Astrocytesmentioning
confidence: 99%
“…VP-As also expressed the stem cell markers Cryab and HOPX, which label inner and outer radial glia during prenatal development (Figure 3c-e). We have previously shown that ILAs express each of these markers (Falcone et al, 2021).…”
Section: Vp-as Express Similar Markers To Ilasmentioning
confidence: 99%
“…Interlaminar astrocytes do not occupy specific territorial domains and overlap with their neighbours. They express markers of radial glia (Pax6, Sox2, and Nestin), as well as astrocytic markers GFAP, S100β, Aqp4, and GLAST in both rodents and hominids (Falcone et al 2021). Grafting human iPSC-derived astrocyte progenitors in the mouse brain results in appearance of GFAP-positive interlaminar astrocytes in layer I of the mouse cortex ( Fig.…”
Section: Morphological Subtypes Of Cortical Astrocytesmentioning
confidence: 98%
“…Interlaminar astrocytes are almost exclusively found in higher primates (although there are descriptions of rudimentary interlaminar astrocytes in mouse (Falcone et al 2021)), and emerge at postnatal stages. Their somata are located in layer I of the cerebral cortex.…”
Section: Morphological Subtypes Of Cortical Astrocytesmentioning
confidence: 99%